2021
DOI: 10.1007/s10157-021-02126-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of combination therapy of tocilizumab and steroid pulse therapy for critical COVID-19 in HD patients

Abstract: Background Critical coronavirus disease 2019 (COVID-19) has a high fatality rate, especially in hemodialysis (HD) patients, with this poor prognosis being caused by systemic hyperinflammation; cytokine storms. Steroid pulse therapy or tocilizumab (TCZ) have insufficient inhibitory effects against cytokine storms in critical cases. This study evaluated the clinical effects and safety of combining steroid pulse therapy and TCZ. Methods From September… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
8
0
2
Order By: Relevance
“…TNFi'lerinin çeşitli vaka serilerinde hemodiyaliz veya periton diyalizi gibi renal replasman tedavisi gören RA hastalarında da güvenli ve etkili olduğu gösterilmiştir 10,12,22,23 . Benzer şekilde tosilizumabın hemodiyalize giren RA hastalarında güvenli olduğunu bildiren daha eski vaka bildirileri 21,24 bulunmaktadır, yanı sıra COVID-19 döneminde hemodiyaliz hastalarında güvenle kullanıldığına dair yeni vaka bildirileri de yapılmıştır 25,26,27 . Serum AA (SAA) üretiminin baskılanması AA amiloidozunun kontrolü için gereklidir 28 .…”
Section: Bulgularunclassified
“…TNFi'lerinin çeşitli vaka serilerinde hemodiyaliz veya periton diyalizi gibi renal replasman tedavisi gören RA hastalarında da güvenli ve etkili olduğu gösterilmiştir 10,12,22,23 . Benzer şekilde tosilizumabın hemodiyalize giren RA hastalarında güvenli olduğunu bildiren daha eski vaka bildirileri 21,24 bulunmaktadır, yanı sıra COVID-19 döneminde hemodiyaliz hastalarında güvenle kullanıldığına dair yeni vaka bildirileri de yapılmıştır 25,26,27 . Serum AA (SAA) üretiminin baskılanması AA amiloidozunun kontrolü için gereklidir 28 .…”
Section: Bulgularunclassified
“…Distintas publicaciones en todo el mundo documentaron la evidencia científica de los beneficios de los GC en este tipo de pacientes [15][16][17] ; sin embargo, también existen estudios en los que se ha observado un efecto negativo, sobre todo en pacientes con comorbilidad [18][19][20] . En el estudio de Provencio et al 21 se hace referencia a que el riesgo de muerte fue significativamente mayor en los pacientes que recibieron GC durante la hospitalización, en comparación con aquellos que no los recibieron (51.3% vs. 25.7%; p < 0.001).…”
Section: Discussionunclassified
“…However, the RECOVERY trial, which included SpO 2 < 92% or oxygen administration in addition to C-reactive protein > 7.5 mg/dL, [ 21 ] and the REMAP-CAP trial in severe patients showed a significant reduction in mortality in the tocilizumab group [ 21 ]. Furthermore, Toda et al reported the efficacy of combining tocilizumab and steroid pulse therapy in dialysis patients [ 22 ]. Further studies are required to determine the appropriate target patients and the timing of administration, and evaluate the possibility of the combination therapy, particularly in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%